A state of secrecy Stasi informers and the culture of surveillance - Lewis, Alison, 1958- (Potomac Books, an imprint of the University of Nebraska Press, 2021)
A series of five interlaced, in-depth biographical studies from across the spectrum of writers-turned-spies recruited by the Stasi.
Keywords: Germany (East). -- Ministerium für Staatssicherheit -- History.; Germany (East). -- Ministerium für Staatssicherheit; Informers -- Germany (East); Authors as spies -- Germany (East); Intelligence service -- Germany (East) -- History.; Service des renseignements -- Allemagne (Est) -- Histoire.; Intelligence service; Informers; Authors as spies; Germany (East); History